Two-layer coating for improved corrosion resistance and hardness
A dual-component waterborne coating system with acrylate polymer particles and varying MFFT addresses the inadequacies of single resin systems by providing enhanced hardness and weathering resistance in two-layer applications.
Patent Information
- Application Number
- CN202380083728.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-20
- Filing Date
- 2023-12-11
- Publication Date
- 2025-07-15
AI Technical Summary
The existing AEH resin systems have shortcomings in providing corrosion resistance and weather resistance, especially in hardness, and it is difficult to achieve a good balance in a single chemical system.
Using a two-component aqueous coating system, including the first and second two-component coating compositions, each containing an aqueous dispersion of acrylic polymer particles absorbing epoxy compounds, by forming two layers of coating on the substrate, each layer has a different minimum film formation temperature and is partially cured above room temperature to form a coating with excellent corrosion resistance and hardness.
The corrosion resistance and hardness of the coating are significantly improved, and a good balance of corrosion resistance, weather resistance and hardness in a single chemical system is achieved, reducing costs and simplifying the process.
Smart Images

Figure CN120322514A_ABST
Abstract
Description
BACKGROUND OF THE INVENTION
[0001] In the paint industry, especially in the industrial paint industry, coatings that are both corrosion-resistant and weather-resistant are often required. Multilayer coatings have been developed to provide a first layer that provides adhesion and corrosion resistance to the substrate. Additional layers are then applied to provide weather resistance, chemical resistance, and / or a desired appearance. Epoxy resins are typically selected for the first layer, while polyurethane resins or acrylic resins are typically used for the upper layers. Different resin chemistries are used because it is difficult to find a single resin chemistry that provides the necessary balance between corrosion resistance and weather resistance.
[0002] Acrylic epoxy hybrid (AEH) resins, such as those disclosed in U.S. Patent No. 8,658,742, have been developed to provide a better balance between corrosion resistance and weather resistance in a single chemical system. These AEH resin systems allow for a single-coat system that provides good corrosion resistance and weather resistance for many applications, such as directly applied to metal coatings.
[0003] However, for some applications, the hardness and / or weather resistance provided by existing AEH resin systems are insufficient. There is a need for a low-cost and simple resin system, such as a single chemical system, that can provide the desired corrosion resistance, weather resistance, and hardness. SUMMARY OF THE INVENTION
[0004] In a first aspect, the present invention relates to a coating system comprising:
[0005] a) a first two-component aqueous coating composition comprising a binder component 1A and a curing component 1B, wherein the binder component 1A comprises a first aqueous dispersion of acrylic polymer particles absorbed with an epoxide compound, wherein the first two-component aqueous coating composition comprises a first coalescent package containing at least one coalescent and has a minimum film formation temperature (MFFT) of less than 5°C;
[0006] b) a second two-component coating composition comprising a binder component 2A and a curing component 2B, wherein the binder component 2A comprises a second aqueous dispersion of acrylic polymer particles absorbed with an epoxide compound, wherein the second two-component aqueous coating composition comprises a second coalescent package containing at least one coalescent and has a minimum film formation temperature (MFFT) of 5°C
[0007] to 25°C.
[0008] In a second aspect, the present invention relates to a method for preparing a coating, the method comprising:
[0009] (i) providing a coating system according to any one of the preceding claims;
[0010] (ii) Apply the first two - part coating composition to a substrate to form a first coating;
[0011] (iii) Cure the first coating at least partially for at least 10 minutes at a temperature above room temperature;
[0012] (iv) Apply the second two - part coating composition over the first coating to form a second coating;
[0013] (v) Cure the second coating at a certain temperature to form a two - layer coating on the substrate. Description of the Drawings
[0014] Figure 1 are photographs of coatings according to embodiments of the present invention and comparative examples, which coatings are subjected to salt spray to determine corrosion resistance.
[0015] Figure 2 are photographs of coatings according to comparative examples, which coatings are subjected to salt spray to determine corrosion resistance. Detailed Description
[0016] In a first aspect, the present invention relates to a coating composition comprising a first two - component aqueous coating composition and a second two - component aqueous coating composition.
[0017] The first two - component aqueous coating composition comprises a binder component 1A and a curing (i.e., cross - linking) component 1B. The binder component 1A comprises a first aqueous dispersion of acrylic polymer particles having absorbed an epoxy compound. As used herein, the term "acrylic" includes (meth)acrylic acid, (meth)acrylic alkyl esters, (meth)acrylamide, (meth)acrylonitrile, and modified forms thereof such as (meth)acrylic hydroxyalkyl esters. The fragment "(meth)acryloyl" means "methacryloyl" and "acryloyl", such that for example, (meth)acrylic acid means both methacrylic acid and acrylic acid, and (meth)methyl acrylate means both methyl methacrylate and methyl acrylate. As used herein, the term "having absorbed an epoxy compound" means that the epoxy compound is at least partially absorbed by the acrylic polymer particles, but does not react with the acrylic polymer particles and is not merely present on the surface of the acrylic polymer particles.
[0018] The second two - component aqueous coating composition comprises a binder component 2A and a curing component 2B. The binder component 2A comprises a second aqueous dispersion of acrylic polymer particles having absorbed an epoxy compound.
[0019] The first aqueous dispersion and the second aqueous dispersion of acrylic polymer particles absorbing an epoxy compound may be the same or different. Preferably, the first aqueous dispersion and the second aqueous dispersion of acrylic polymer particles absorbing an epoxy compound are the same.
[0020] Preferably, the first aqueous dispersion and the second aqueous dispersion of acrylic polymer particles absorbing an epoxy compound comprise an aqueous dispersion of acrylic polymer particles absorbing a thermosetting compound having at least two epoxy groups. As used herein, the term "thermosetting compound" means a compound that will undergo a chemical reaction to form a thermoset compound that has different chemical and physical properties and does not undergo a reversible thermal transition upon exposure to heat.
[0021] The absorbed thermosetting compound preferably has a plurality of epoxy groups; more preferably, the thermosetting compound is a novolak resin, a di-, tri- or tetra-glycidyl ether or a di-, tri- or tetra-glycidyl ester.
[0022] Examples of suitable thermosetting compounds include the diglycidyl ether of bisphenol A, the diglycidyl ether of bisphenol F, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, the diglycidyl ester of phthalic acid, 1,4-cyclohexanedimethanol diglycidyl ether, 1,3-cyclohexanedimethanol diglycidyl ether, the diglycidyl ether of hexahydrophthalic acid and novolak resins, and combinations thereof. A commercially available thermosetting compound is D.E.R. 331 liquid epoxy resin (available from Olin Corporation).
[0023] The aqueous dispersion of acrylic polymer particles (i.e., latex) can be obtained by free radical emulsion or suspension addition polymerization or by dispersing a preformed polymer into an aqueous medium under shear. Examples of suitable latexes include acrylic and styrene-acrylic based latexes.
[0024] The acrylic polymer particles may further comprise an anti-coalescence functional group, which refers to a hydrophilic group that is sufficiently non-reactive with epoxy groups (and ester groups, if present) such that the latex particles are stable upon 10 days of thermal aging at 60 °C. The term "stable upon 10 days of thermal aging at 60 °C" as used herein means that the particle size of the latex after 10 days of thermal aging at 60 °C is no more than 30% greater than the particle size prior to such thermal aging studies.
[0025] Anticoalescence functional groups can be incorporated into polymer particles using monomers containing anticoalescence functional groups (anticoalescence monomers), but such groups can also be incorporated by grafting. Anticoalescence groups are considered effective because they are hydrophilic under thermal aging conditions and do not react with epoxy groups. General classes of such groups include amide groups, acetoacetoxy groups, and strong proton acids whose pH is adjusted to form their conjugate bases.
[0026] Specific examples of anticoalescence monomers include acrylamide, ethyl phosphate methacrylate, sodium styrene sulfonate, ethyl acetoacetoxy methacrylate, and acrylamido-methyl-propane sulfonate. When present, the concentration of anticoalescence functional groups in the polymer is preferably sufficient to stabilize the thermoplastic polymer under thermal aging conditions, preferably 0.5 wt%, and more preferably 1 wt% to preferably 10 wt%, and more preferably up to 5 wt% based on the weight of the polymer.
[0027] Monomers suitable for preparing acrylic latexes include acrylates and methacrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate and combinations thereof. In addition, acrylic latexes can also include structural units of other monomers such as styrene and acrylonitrile. As used herein, the term "structural unit" refers to the residue of the named monomer after polymerization. Structural units of one or more acid monomers can also be included, most notably acrylic acid, methacrylic acid, and itaconic acid. Monomers capable of conferring co-curable functional groups can also be included, such as glycidyl acrylate and glycidyl methacrylate.
[0028] It may be advantageous to include a chain transfer agent in the latex preparation. Examples of chain transfer agents include, but are not limited to, dodecyl mercaptan, butyl mercaptopropionate, methyl mercaptopropionate, mercaptopropionic acid, etc.
[0029] In certain embodiments, it may be advantageous to incorporate copolymerized polyethylenically unsaturated monomer groups into the polymer. Polyethylenically unsaturated monomers include, for example, allyl (meth)acrylate, diallyl phthalate, 1,4-butanediol di(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and divinylbenzene. It can be particularly advantageous to incorporate such monomer groups non-uniformly into the polymer to form multiphase polymer particles, resulting in core-shell, hemispherical, or occluded morphologies.
[0030] The aqueous dispersion of acrylic polymer particles absorbing an epoxide (i.e., absorbed latex) is separately prepared using conventional emulsion polymerization techniques advantageously and then combined with a thermosetting compound, which may be pure or in the form of an aqueous emulsion, preferably in the form of an aqueous emulsion, more preferably in the form of a micronized aqueous emulsion. When the thermosetting compound is added as an aqueous emulsion, the emulsion is stabilized with a stabilizing amount of surfactant, preferably at a concentration in the range of about 0.5 to about 10 wt%. Nonionic surfactants are preferred and include APEO-free nonionic wetting agents such as polyalkylene oxide block copolymers, polyoxyethylene alkyl ethers, glucoside alkyl ethers, fatty acid esters, glycerol alkyl esters, sorbitan alkyl esters, and polyoxyethylene alkylphenol ethers, including commercially available wetting agents such as TRITON TM X-405 octylphenol ethoxylate (a trademark of Dow Chemical Company or its affiliates). When the thermosetting compound is combined with the latex as a pure compound, absorption is facilitated by stirring at room temperature or above room temperature.
[0031] Based on the total weight of the latex, a high solids content absorbed latex, i.e., a latex having a solids content of at least 40 wt% and especially 45 wt% to 60 wt% can be used in the present invention.
[0032] The absorbed latex composition can be used as part of a two-component formulation (i.e., binder component 1A or 2A), and the second component is a curing (i.e., crosslinking) component (1B or 2B) added prior to use, which cures or solidifies the thermosetting compound. Thus, the binder components 1A, 2A of the present invention are substantially free of curing agents; i.e., the concentration of the compound promoting the ring opening of ethylene oxide is not sufficient to destabilize the thermosetting compound. Preferably, based on the total weight of the absorbed latex composition, the absorbed latex composition contains no more than 0.05 wt%, more preferably no more than 0.005 wt%, and most preferably 0 wt% of a curing agent.
[0033] Preferably, the absorbed latexes in the binder components 1A and 2A are cured with a water-compatible external curing agent comprising curing components 1B and 2B. Preferably, the absorbed latex is cured with a carboxylic acid-based acrylic acid. Examples of carboxylic acid-based acrylic acids include, for example, acrylic polymer emulsions, which include, but are not limited to, structural units derived from carboxylic acids such as, for example, methacrylic acid, itaconic acid, and acrylic acid, and acrylic monomers, including methyl acrylate, ethyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, isooctyl acrylate, n-decyl acrylate, isodecyl acrylate, tert-butyl acrylate, methyl methacrylate, butyl methacrylate, hexyl methacrylate, isobutyl methacrylate, isopropyl methacrylate, 2-hydroxyethyl acrylate, acrylamide, acrylonitrile, methacrylonitrile, isobornyl acrylate, n-propyl methacrylate, sec-butyl methacrylate, cyclohexyl methacrylate, tert-butylaminoethyl methacrylate, stearyl methacrylate, glycidyl methacrylate, dicyclopentenyl methacrylate, phenyl methacrylate, and styrene. For example, the acrylic polymer dispersion may comprise a styrene-acrylic polymer.
[0034] Preferably, the acrylic polymer dispersion comprises 35 wt% to 70 wt%, and more preferably 40 wt% to 65 wt%, of acrylic solids based on the total weight of the acrylic polymer dispersion. Preferably, the acrylic particles have a weight average particle size in the range of 60 nm to 450 nm, and an acid content in the range of 0.1 wt% to 15 wt% of acid monomers, based on the weight of the acrylic monomers, a weight average molecular weight in the range of 50,000 g / mol to 5,000,000 g / mol, and a glass transition temperature (Tg) in the range of 7 °C to 100 °C, as measured by differential scanning calorimetry (DSC). The pH of the acrylic polymer dispersion is in the range of 6 to 10.
[0035] Based on the number of moles of epoxy groups and the number of moles of carboxylic acid, the amount of curing agent used typically changes from about 1:1 to 4:1 in the epoxy resin - carboxylic acid stoichiometric ratio. Preferably, the curing agent in the curing component 1B in the first two - component coating composition is present in an amount of about 1.75:1 to 2.5:1 based on the number of moles of epoxy groups and the number of moles of carboxylic acid in the first two - component coating composition, and the curing agent in the curing component 2B is present in the second two - component aqueous coating composition in an amount such that the stoichiometry between the epoxy groups and the acid groups is in the range of 1:1 to 1.5:1 based on the number of moles of epoxy groups and the number of moles of carboxylic acid in the second two - component aqueous coating composition. More preferably, the curing agent in the curing component 1B in the first two - component coating composition is present in an amount of about 2.0:1 to 2.5:1 based on the number of moles of epoxy groups and the number of moles of carboxylic acid in the first two - component coating composition, and the curing agent in the curing component 2B is present in the second two - component aqueous coating composition in an amount such that the stoichiometry between the epoxy groups and the acid groups is in the range of 1:2 to 1.4:1 based on the number of moles of epoxy groups and the number of moles of carboxylic acid in the second two - component aqueous coating composition.
[0036] Preferably, the binder components 1A and 2A comprise a similar acrylic - type latex absorbed with an epoxy compound, and the curing components 1B and 2B comprise a similar curing agent. In other words, the coating system preferably comprises a single chemical resin system.
[0037] The first two - component aqueous coating composition and the second two - component aqueous coating composition further comprise a first coalescent package and a second coalescent package, respectively. Each coalescent package includes at least one coalescent. As used herein, the term "coalescent" refers to a non - volatile or slow - evaporating solvent that causes polymer particles to fuse into a continuous film under ambient conditions. At least one coalescent in each coalescent package included in the coalescent packages may be the same or different. Preferably, the first coalescent package and the second coalescent package comprise the same coalescent.
[0038] Examples of suitable coalescents include 2 - n - butoxyethanol, dipropylene glycol n - butyl ether, propylene glycol n - butyl ether, dipropylene glycol methyl ether, propylene glycol methyl ether, propylene glycol n - propyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, triethylene glycol monobutyl ether, dipropylene glycol n - propyl ether, n - butyl ether, or mixtures thereof. Preferred coalescents include dipropylene glycol n - butyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, n - butyl ether, or mixtures thereof. Commercially available coalescents include, for example, OPTIFILM 400 and TEXANOL coalescent, both available from Eastman Chemical Company.
[0039] Preferably, the second coalescent package contains a lower amount of coalescent than the first coalescent package. At least one coalescent in the first coalescent package is present in an amount in the range of 10 wt% to 30 wt%, preferably 15 wt% to 25 wt%, based on the total weight of the solids in the first binder component 1A and the first curing component 1B, where the total solids amount does not include any additional components (e.g., pigments present in the first two-component coating composition). At least one coalescent in the second coalescent package is present in an amount in the range of 2 wt% to 10 wt%, preferably 4 wt% to 9 wt%, based on the total weight of the solids in the second binder component 2A and the second curing component 2B, where the total solids amount does not include any additional components (e.g., pigments present in the second two-component coating composition).
[0040] The first two-component coating composition and the second two-component coating composition have different minimum film formation temperatures (MFFT). MFFT is the lowest temperature at which polymer particles on an aqueous dispersion will coalesce with each other and form a continuous film when volatile components (e.g., water) evaporate. MFFT can be measured according to GB / T9267-2008. The first two-component coating composition is below 5 °C. Preferably, the MFFT of the first two-component coating composition is in the range of -10 °C to 5 °C. The MFFT of the second two-component coating composition is 5 °C to 25 °C, preferably 5 °C to 15 °C.
[0041] The first two-component coating composition and the second two-component coating composition according to the present invention may also contain one or more of the following additives: solvents; fillers; pigments such as titanium dioxide, mica, calcium carbonate, silica, zinc oxide, ground glass, aluminum trihydrate, talc, antimony trioxide, fly ash, and clay; polymer-encapsulated pigments such as polymer-encapsulated or partially encapsulated titanium dioxide, zinc oxide, or lithopone; polymers or polymer emulsions adsorbed or bound to the surface of pigments such as titanium dioxide; hollow pigments, including pigments having one or more voids; dispersants such as amino alcohols and polycarboxylates; surfactants; defoamers; preservatives such as biocides, mildew inhibitors, fungicides, algaecides, and combinations thereof; flow agents; leveling agents; and additional neutralizing agents such as hydroxides, amines, ammonia, and carbonates.
[0042] The volatile organic compound (VOC) content of the first two-component coating composition and the second two-component coating composition can also be different. For example, the VOC content of the first two-component coating composition can be in the range of 0.75 lb / gal to 1.25 lb / gal, and the VOC content of the second two-component coating composition can be in the range of 0.25 lb / gal to 0.5 lb / gal.
[0043] Similarly, the pigment volume concentration (PVC) of the first two-component coating composition and the second two-component coating composition can be different. The PVC can be calculated by the following equation:
[0044]
[0045] For example, the PVC of the first two-component coating composition can be in the range of 15% to 20%, and the PVC of the second two-component coating composition can be in the range of 7.5% to 12.5%.
[0046] A second aspect of the present invention relates to a method of preparing a coating. The method includes providing the first and second aqueous coating compositions as described above.
[0047] A first coating is formed by applying the first two-part coating composition to a substrate. The first coating is at least partially cured at a temperature above room temperature for at least 10 minutes. Preferably, the curing temperature is at least 50°C, and more preferably at least 60°C, and the curing time is preferably at least 15 minutes. Before curing, the first layer can be flash evaporated at room temperature.
[0048] After the first coating is at least partially cured, a second layer having the second two-component coating composition is applied over the first layer. Then the second layer is cured at a temperature above room temperature for at least 10 minutes. Preferably, the curing temperature is at least 50°C, more preferably at least 60°C, and the curing time is preferably at least 15 minutes. The second layer can be flash evaporated at room temperature before curing to allow the evaporation of volatile components.
[0049] Preferably, the substrate is a metal substrate. The metal substrate can be bare metal (e.g., the coating is a direct-to-metal coating) or a primed metal substrate (e.g., a metal substrate coated with a zinc-rich primer).
[0050] Examples - The following examples are for illustrative purposes only and are not intended to limit the scope of the present invention. The following materials were used in the examples:
[0051] AEH-1 is an AEH dispersion with a solids content of 53.9%, an epoxy equivalent of 312 g / eq based on the solids weight, and a pH of 7.
[0052] AEH-2 is an AEH dispersion with a solids content of 52.2%, an epoxy equivalent of 468 g / eq based on the solids weight, and a pH of 7.
[0053] SAP is a carboxylic acid-functional styrene-acrylic polymer dispersion with a solids content of 49.5% and an acid equivalent of 2457 g / eq based on the polymer solids, and is used as a curing agent.
[0054] DOWANOL TMDPnB is dipropylene glycol monobutyl ether available from The Dow Chemical Company and is used as a coalescent.
[0055] OPTIFILM 400 is a coalescent available from Eastman Chemical Company.
[0056] OROTAN TM 681 is polymethacrylic acid with a hydrophobic comonomer available from The Dow Chemical Company and is used as a dispersant.
[0057] ACRYSOL TM RM-12W is a nonionic polyurethane rheology modifier available from The Dow Chemical Company.
[0058] TEGO Airex 902W is a polyether silicone copolymer emulsion available from Evonik Corporation and is used as an antifoaming agent.
[0059] Ti-PURE R-706 is a titanium dioxide pigment available from Chemour Company.
[0060] TAMOL TM 681 is a hydrophobic copolymer dispersant available from The Dow Chemical Company.
[0061] TRITON TM HW-1000 is a nonionic surfactant available from The Dow Chemical Company.
[0062] ANCAMINE K-54 is a tris-(dimethylaminomethyl) phenol curing agent available from Evonik Corporation.
[0063] XIAMETER TM OFS-6020 is an aminoethylaminopropyltrimethoxysilane coupling agent available from The Dow Chemical Company.
[0064] Preparation of the primer coating composition
[0065] Prepare pigment grindings for basecoat 1, basecoat 2 and topcoat according to Table 1 below. Add the following ingredients to a 1L stainless steel container and mix on a disperser with a 2” cowles blade at low shear (1000 rpm) until homogeneous (about 5 minutes): 299.56 g deionized water, 11.68 g ammonia (28%), 7.49 g Foamex 1488, 48.13 g Tamol 681 and 9.99 g Triton HW1000. After about 5 minutes, slowly add 1123.15 g TiPure R706 under shear. Gradually increase the mixing speed to achieve good vortex. After adding all the TiO2, stop the disperser so that the sides of the blade, shaft and container can be scraped with a metal spatula. Then turn on the disperser and increase the speed to about 2000 rpm. After about 15 minutes, when the Hegman gauge reading is 7 - 8 units, the mixing is complete. Then the pigment grindings are ready to be added to the formulations in Table 2 listed below.
[0066] Table 1
[0067] Component Weight (g) Deionized water 499.27 Ammonia (28%) 19.47 TEGO Foamex 1488 12.48 <![CDATA[TAMOL TM 681]]> 80.22 <![CDATA[TRITON TM HW1000]]> 16.64 Ti-Pure R-706 TiO2 1871.91 Total 2500
[0068] Prepare two basecoat paint compositions, basecoat 1 and basecoat 2, using two different acrylic epoxy hybrids AEH - 1 and AEH - 2 respectively. Prepare the Part B side mixtures in plastic containers with appropriate content sizes (8 oz. to 32 oz.) using a metal paddle (1” diameter) on a laboratory mixer set at an appropriate speed (500 rpm - 1000 rpm) to maintain good vortex. Add the first ingredient on a laboratory balance and add additional ingredients while mixing to achieve good incorporation. After adding the last ingredient, remix the mixture at about 1100 rpm for 15 minutes. Let the Part B side equilibrate overnight, then mix with a tongue depressor and prepare the paint.
[0069] Table 2
[0070]
[0071] The properties of basecoat 1, basecoat 2 and topcoat are shown in Table 3.
[0072] Table 3
[0073] Binder 1 Binder 2 Topcoat Characteristic Value Value Value Molar ratio (epoxy / acid) 2.3 / 1 2.3 / 1 1.3 / 1 % PVC 17.0 17.0 10.0 VOC (lb / gal) 0.91 0.91 0.33 % Weight solids 52.8 52.9 49.2 % Volume solids 40.9 40.9 40.8 % Coalescing agent 19.7 19.6 6.0
[0074] Two-layer coated metal sample
[0075] Samples were prepared by coating a phosphated (BONDERITE 1000) cold-rolled steel substrate with two layers of paint. In Example 1, the first coat of primer 1 was applied, followed by the topcoat paint. Example 2 was prepared by coating the substrate with the first layer of primer 2 and the second layer of topcoat. Comparative Example 1 was prepared by coating the substrate with the first layer of primer 2 and the second layer of primer 1. To prepare Comparative Example 2, two layers of topcoat were applied. In each of the 2-layer paint samples, the first layer was applied and flash-evaporated at room temperature for 30 minutes, and then cured at 80 °C for 20 minutes. Then, the sample was cooled for 1 to 2 hours until it reached room temperature before applying the second layer. The second paint was flash-evaporated at room temperature for 30 minutes and then cured at 80 °C for 20 minutes. After curing, the coated metal samples were held at room temperature for 7 days before testing.
[0076] The corrosion resistance of the samples was determined by subjecting the samples to salt spray for 504 hours and then scratching. As Figure 1 shown, Examples 1 and 2 and Comparative Example 1 exhibited good corrosion resistance, while Comparative Example 2, which consisted of two layers of topcoat, exhibited poor corrosion resistance.
[0077] The hardness of each of the coated metal samples was tested using a Persoz pendulum according to ASTM-D4366. The results of the Persoz hardness tests are shown in Table 4 below, which also shows that each sample had relatively similar thickness and gloss, as tested by a micro-TRI-gloss machine (BYK Company). The hardness of Examples 1 and 2 was significantly improved compared to the 2-layer paint of Comparative Example 1, which lacked the layer containing the topcoat.
[0078] Table 4
[0079]
[0080] Single-layer coated metal sample
[0081] Single-layer coated metal samples were prepared on a phosphated (BONDERITE 1000) cold-rolled steel substrate. Comparative Example 3 was prepared by coating the metal substrate with primer 2. Comparative Example 4 was prepared by blending primer 2 and topcoat in a 1:1 ratio and forming the paint as a single layer on the substrate. Comparative Example 5 was prepared by coating the metal substrate with a single layer of topcoat. Each sample was prepared by applying a single layer on the substrate, flash-evaporating at room temperature for 30 minutes and curing at 80 °C for 20 minutes, and then curing at room temperature for 7 days before testing.
[0082] The corrosion test and hardness test were repeated for the single-layer coated metal samples. For the corrosion test, the samples were exposed to salt spray for 552 hours before scratching. As Figure 2As shown, Comparative Examples 4 and 5 both showed poorer corrosion resistance compared to Comparative Example 3. The results of the hardness tests are shown in Table 5 below.
[0083] Table 5
[0084]
[0085] Although Comparative Example 4 showed slightly better hardness than Comparative Example 3, the hardness of Comparative Example 4 was significantly lower than that of the two-layer coated metal sample of Example 2.
[0086] A direct comparison between Example 2 and Comparative Example 4 clearly shows that using different formulations in two separate layers (with at least partial curing between each layer) can significantly improve the corrosion resistance and hardness of the resulting coating.
Claims
1. A coating system, said coating system comprising: a) A first two-component aqueous coating composition, said first two-component aqueous coating composition comprising a binder component 1A and a curing component 1B, wherein said binder component 1A comprises a first aqueous dispersion of acrylic polymer particles absorbed with an epoxide, wherein said first two-component aqueous coating composition comprises a first coalescent package containing at least one coalescent and has a minimum film formation temperature (MFFT) of less than 5 °C; b) A second two-component coating composition, said second two-component coating composition comprising a binder component 2A and a curing component 2B, wherein said binder component 2A comprises a second aqueous dispersion of acrylic polymer particles absorbed with an epoxide, wherein said second two-component aqueous coating composition comprises a second coalescent package containing at least one coalescent and has an MFFT of 5 °C to 25 °C.
2. The coating system according to claim 1, wherein said first aqueous dispersion of acrylic polymer particles absorbed with an epoxide is the same as said second aqueous dispersion of acrylic polymer particles absorbed with an epoxide.
3. The coating system according to claim 1 or 2, wherein said curing component 1B and said curing component 2B are selected from carboxylic acid-based acrylic curing agents.
4. The coating system according to claim 3, wherein said curing component 1B is present in said first two-component aqueous coating composition in an amount such that the molar ratio of epoxy groups to carboxylic acid groups in said first two-component aqueous coating composition is in the range of 1.75:1 to 4:1, and said curing component 2B is present in said second two-component aqueous coating composition in an amount such that the molar ratio of epoxy groups to carboxylic acid groups in said second two-component aqueous coating composition is in the range of 1:1 to 1.5:
1.
5. The coating system according to any one of the preceding claims, wherein said curing component 1B is the same as said curing component 2B.
6. The coating system according to any one of the preceding claims, wherein said first coalescent package is present in an amount of 10% to 30% by weight based on the total weight of solids in said first binder component 1A and said first curing component 1B in said first two-component coating composition, and said second coalescent package is present in an amount of 2% to 10% by weight based on the total weight of solids in said second binder component 2A and said second curing component 2B in said second two-component coating composition.
7. The coating system according to claim 6, wherein said first coalescent package is present in an amount of 15% to 25% by weight based on the total weight of solids in said first binder component 1A and said first curing component 1B in said first two-component coating composition, and said second coalescent package is present in an amount of 4% to 9% by weight based on the total weight of solids in said second binder component 2A and said second curing component 2B in said second two-component coating composition.
8. A coating system according to any one of the preceding claims, wherein the second two-component coating composition has a MFFT of 5 °C to 15 °C.
9. A coating system according to any one of the preceding claims, wherein the first two-component coating composition has a VOC content in the range of 0.75 lb / gal to 1.25 lb / gal, and the second two-component coating composition has a VOC content in the range of 0.25 lb / gal to 0.5 lb / gal.
10. A coating system according to any one of the preceding claims, wherein the first two-component coating composition has a pigment volume concentration (PVC) of 15% to 20%, and the second two-component coating composition has a PVC of 7.5% to 12.5%.
11. A method of preparing a coating, the method comprising: (i) providing a coating system according to any one of the preceding claims; (ii) applying a first two-part coating composition to a substrate to form a first coating; (iii) at least partially curing the first coating at a temperature above room temperature for at least 10 minutes; (iv) applying a second two-part coating composition over the first coating to form a second coating; (v) curing the second coating at a temperature above room temperature for at least 10 minutes to form a two-layer coating on the substrate.
12. The method according to claim 11, wherein the substrate comprises a metal substrate.
13. The method according to claim 12, wherein the metal substrate comprises a bare metal substrate or a primed metal substrate.
14. The method according to any one of claims 11 to 13, wherein step (iii) of at least partially curing the first coating comprises at least partially curing the first coating at a temperature of at least 50 °C for at least 15 minutes.
15. The method according to any one of claims 11 to 14, wherein step (v) of curing the second coating comprises curing the second coating at a temperature of at least 50 °C for at least 15 minutes.
Citation Information
Patent Citations
Epoxy resin imbibed polymer particles
US8658742B2